Comparison of Efficacy of Epinephrine to Salbutamol and Ipratropium Bromide Combined in Acute Bronchiolitis - Ahsan Iqbal Danish, Qaiser Shehzad Humayoun, Asad Shabbir, Israr Liaquat, Muhammad Hafeez, Ibrahim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Epinephrine, an alpha receptor agonist, has been suggested to be a supreme bronchodilator. A biologically active drug name Ipratropium bromide is helpful for the treatment of bronchiolitis among infants and improves on the signs and symptoms of bronchiolitis. Objective: To compare effectiveness of combined nebulized salbutamol with nebulized adrenaline and ipratropium bromide in bronchiolitis affected children in terms of mean improvement in RDAI score. Methodology: After approval from ethical committee this randomized control trial of 6 month duration is carried out by Randomization of patients in 2 groups. Group A received salbutamol (0.15mg/kg) combined with ipratropium bromide (250 micrograms per dose) with isotonic sodium chloride solution 0.9% (2 mL) and Group B received a dose of epinephrine (0.5mg/kg in concentration of 1:1000(max 5 mg), distributed by nebulizer with the help of a face mask with continuous oxygen flow at 6L/min Prior to each drug administration and at 30 mints, the researcher evaluated the condition of infant’s and records the respiratory rate, RDAI score9, heart rate and SaO2. RESULTS: Comparison of effectiveness of combined nebulized salbutamol with nebulized adrenaline and ipratropium bromide in bronchiolitis affected children in terms of mean improvement in RDAI score shows that at baseline in Group-A it was 10.73+1.59 and 10.98+1.42, p value was 0.27, it was reduced after 30 minutes of treatment in Group-A 3.23+0.52 and 2.67+0.47 in Group-B, p value was 0.001. Conclusion: We concluded that Epinephrine is better than salbutamol and ipratropium combined in terms of mean improvement in RDAI score